Differential effects of emotional labor strategies on university counselors’ job burnout: the dual role of psychological capital as a mediator and a moderator - Song, Yunbo; Yang, Honglin (Frontiers in Psychology, 2026)
BackgroundUniversity counselors are a high-risk group for job burnout, and how to alleviate their job burnout has become an increasingly urgent issue. Previous studies have paid less attention to the differential effects of emotional labor strategies on the job burnout of the counselors. This study aims to explore the association between various emotional labor strategies and job burnout among counselors, as well as the underlying mechanisms involving psychological capital as mediator and moderator.MethodsThis study selected 747 counselors from six public universities in a western Chinese province using a cross-sectional design. Standardized scales were employed to measure emotional labor strategies, psychological capital, and job burnout. Data analysis was performed using the SPSS PROCESS macro (v4.3) to examine the dual role of psychological capital, separately testing its mediating effect in the relationship between emotional labor strategies and job burnout, and its moderating effect on their direct association.ResultsThe study results indicated that surface acting was significantly positively related to job burnout, whereas deep acting and natural expression were significantly negatively related to job burnout. This relationship was influenced by the mediating role of psychological capital, with effect sizes ranked as follows: deep acting > natural expression > surface acting. Furthermore, psychological capital moderated the relationships between surface acting/natural expression and job burnout.ConclusionResults indicated that surface acting was significantly associated with job burnout, whereas deep acting and natural expression were negatively associated with job burnout. Psychological capital played a dual role: it not only mediated the relationship between emotional labor and job burnout, but also buffered the negative effect of surface acting while enhancing the protective effect of natural expression. Therefore, fostering psychological capital and promoting adaptive emotional labor strategies represent promising avenues for preventing job burnout among university counselors.